Abuse and misuse of second‐generation antipsychotics: An analysis using VigiBase, the World Health Organisation pharmacovigilance database. Issue 10 (8th June 2022) - Roy, Sophie; Charreteur, Robin; Peries, Marianne; Kheloufi, Farid; Eiden, Céline; Nagot, Nicolas; Donnadieu‐Rigole, Hélène; Micallef, Joëlle; Peyrière, Hélène
Abstract : The study aim was to assess the abuse/misuse potential of second‐generation antipsychotics (SGAPs) using VigiBase data. We extracted individual case safety reports of "Drug abuse, dependence and withdrawal" involving SGAPs up to June 2018. We assessed disproportionate reporting by calculating the information component, considering the lower end of the 95% credibility interval for the information component (IC025 ), and the proportional reporting ratio. We identified 1683 individual case safety reports recorded as "abuse, dependence and withdrawal" involving SGAPs, mainly quetiapine ( n = 1089) and olanzapine ( n = 209). The disproportional reporting indicators highlighted an association between "Drug abuse and dependence", and quetiapine, olanzapine and ziprasidone, as indicated by the IC025 (2.263, 0.259 and 1.051, respectively) and proportional reporting ratio values (3.929, 1.020 and 1.334, respectively). The abuse/misuse potential is confirmed for quetiapine and olanzapine and highlighted for the first time for ziprasidone. Physicians should consider these risks when prescribing these antipsychotics, especially to patients with history of drug abuse.